Makna Dan Nilai Dalam Tradisi Pelet Betteng Masyarakat Suku Madura Desa Sungai Malaya Kabupaten Kubu Raya - Ahmad Imamul Arifin; Edwin Mirzachaerulsyah; Ika Rahmatika Chalimi; Sulistyarini; Andang Firmansyah (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
The Betteng Pellet Tradition is a tradition of the Madurese people for those who are entering four to seven months of pregnancy for their first child. The purpose of this study was to describe the meaning and value of the Betteng Pellet tradition in the Madurese Tribe Community in Sungai Malaya Village, Sungai Ambawang District, Kubu Raya. This study uses a qualitative method with a descriptive-ethnographic approach. Data collection techniques used are observation, interviews and documentation. So that this research can be realized the implementation of this tradition is marked by the demons of several community leaders (Ustadz / Kyai) and the community, this tradition is as a song as well as a way in seeking blessings, fluency and convenience, and has value in strengthening family ties, creating a sense of togetherness, caring for friendship and most importantly maintaining the betteng pellet tradition so that its existence continues to be a necessity for the Madurese people as well as providing an understanding to the next generation about the purpose and importance of the betteng pellet tradition as a legacy of the ancestors or ancestors of the Madurese people.